Quem controla o saneamento?: um estudo do controle social das políticas públicas de saneamento em quatro municípios da Bacia do Rio das Velhas - MG - Ana Piterman (2008)
The aim of this study is to examine the inclusion of the sanitation topic when it comes to the sanitation, urban policies, health, cities, habitation and environment municipal councils´s approach and performance, that is, it searches to understand the local reality and society´s behavior as transforming agents within the formal municipal authorities ofsocial control. Besides, it looks into the dynamics of the municipal councils as the arena of the full representative citizenship performance on the sanitation topic.bFirstly, the respective councils in all the selected municipalities belonging to the Velhas River Basin were investigated for their existence. For that purpose, four municipalities presenting disparity regarding the existence of councils - Contagem, Nova Lima, Sete Lagoas and Vespasiano were selected.bField research of qualitative nature and documental research as minutes of meetings and paperwork issued by the councils were made. Semi-structured interviews for the acquisition of the previously chosen counselors´ perception (chairman and users´ representatives) on their performance and the importance given to the sanitation topic were used.bThe discourse samples were analyzed considering the speech of the interviewed subjects which revealed that the several municipal councils are marginal to the implementation process of the sanitation public policies. This study points out insufficiencies and precarious premises in the political, judicial and administrative organization of the councils, besides issues of structural order. Last, this research suggests some alternatives aiming at the improvement and strengthening of the municipal councils´ dynamics as a tool for the social control over the State, highlighting not only the need to a continuous education, the perfecting of the participation mechanisms, but also broad access to information.